2017
DOI: 10.1186/s13023-017-0608-2
|View full text |Cite
|
Sign up to set email alerts
|

Developing and evaluating rare disease educational materials co-created by expert clinicians and patients: the paradigm of congenital hypogonadotropic hypogonadism

Abstract: BackgroundPatients with rare diseases face health disparities and are often challenged to find accurate information about their condition. We aimed to use the best available evidence and community partnerships to produce patient education materials for congenital hypogonadotropic hypogonadism (CHH) and the olfacto-genital (Kallmann) syndrome (i.e., CHH and defective sense of smell), and to evaluate end-user acceptability. Expert clinicians, researchers and patients co-created the materials in a multi-step proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 24 publications
0
44
0
1
Order By: Relevance
“…Patients and families have helped develop training programs for patients/families by identifying key content areas [ 43 , 44 ]. More opportunities were reported for organizations which have been involved in sharing informational resources with patients, families, and health care professionals, often through websites, toll-free hotlines, and mentoring programs [ 22 24 , 40 , 45 – 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients and families have helped develop training programs for patients/families by identifying key content areas [ 43 , 44 ]. More opportunities were reported for organizations which have been involved in sharing informational resources with patients, families, and health care professionals, often through websites, toll-free hotlines, and mentoring programs [ 22 24 , 40 , 45 – 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…(2014) also found this, stating that gaining an insight into how someone copes with the day to day life of living with a rare disease would enable a deeper understanding and encourage more sympathetic communication [ 12 ]. Rare disease patients often experience a shift in their relationship with health professionals as they and their carers take on the role as the ‘experts’ [ 41 ]. Budych et al (2012) have shown improved outcomes will result from care providers recognising and acknowledging patient’s expertise and being willing to partner with them in the decision making around treatment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CDG and other groups who have been at the margins of decision-making, this may require the creation of participatory spaces specifically designed to enable all stakeholders to voice their concerns, find middle ground and jointly deliberate on policies, care and research sensitive to their needs, values and preferences [ 43 ]. In other words, it may require spaces in which formerly detached groups can come together to establish bidirectional partnerships [ 44 ] and uncover the elements of expert and patient knowledge that are key for the co-production of patient-centred care and research.…”
Section: Discussionmentioning
confidence: 99%